Physical to biological building blocks in hand & microsurgery: the facts, the face, the facility, the field…and the future - Syed Waseem Ahmad, Sharifah Roohi; Ahmad, Waseem (Universiti Putra Malaysia Press, 2018)
The hand is a truly remarkable instrument-an organ of perception (feel, touch and much more), performance (power grip and fine motor functions), perspiration (sweating assists us in handling items and reducing body temperature), presentation and even communication. Second to the face the most commonly presented part of the body is the hand, thus its appearance of normalcy is crucial. Many a time when we are unable to verbalise our thoughts, we convey our messages, knowingly or otherwise, through non-verbal hand gestures as well as body language. Meanwhile, in dance forms and miming the hands are essential aspects of communication. Similarly sign language is basically that-an entire language communicated via the hands! Anatomically, due to the high density of nerve fibres at the fingertip, digits also aid in stereognosis which enables the blind to "see" and the deaf to "hear" (Alpenfels EJ 1955). The fact that the hand is structurally positioned at the extreme end of the upper limb, to enable it to reach out approximately one metre away from the body, however, makes it extremely susceptible to injury. Injury to the hand and wrist is devastating. All it takes is to imagine a day in one's life without the right or even left hand. It becomes evident that a major portion of our lives and activities of daily living are dependent on us being able to have complete hand (and upper limb) function. In order for us to get through the day, there are numerous bimanual activities we perform without a thought. Even a minor papercut precludes us from continuing with these normally. Thus, hand injuries from the fingertip to the shoulder are functionally and emotionally distressing and need to be addressed immediately. Most importantly the injury or pathology needs to be treated right the first time.